If it's not what You are looking for type in the equation solver your own equation and let us solve it.
2(1+3y)+5=13+5y
We move all terms to the left:
2(1+3y)+5-(13+5y)=0
We add all the numbers together, and all the variables
2(3y+1)-(5y+13)+5=0
We multiply parentheses
6y-(5y+13)+2+5=0
We get rid of parentheses
6y-5y-13+2+5=0
We add all the numbers together, and all the variables
y-6=0
We move all terms containing y to the left, all other terms to the right
y=6
| 4.n=672 | | 7x+1.5=11.5 | | 120–5x=70 | | 179h-44=45 | | Y=60+1.6x | | 17x-(7x-6)=26 | | 9(4w−3)= | | 4m-19=-59 | | 9=9(a-9) | | 102=-6(64v-4)+6 | | 67=7+5x | | 5(x-1)+54=2x | | 4(y+17)=-72 | | 4(x+12)=-12 | | (x)/(4)-3=9 | | 5/y-7=3/y-5 | | 10-7/8x=17 | | 283=233-u | | 2(x-7)+2x=6x+5 | | 4/5x+3/10x=-3+7 | | -2x+5=35-4x | | 4(4y+3)-(y-5)=62 | | -9y+12=-5(y-4) | | $18.75=3n | | X+2(x+7)=3x-7 | | 45+3n=-5n-3 | | 5(2x-9)=23 | | 23/8x-1=-4 | | 6z+10=94 | | 4(x+2=-12 | | 16x+20=15x=60 | | 2x+18+5x–6=180 |